4′-Ethynyl-2-fluoro-2′-deoxyadenosine, MK-8591: a novel HIV-1 reverse transcriptase translocation inhibitor. Issue 4 (July 2018) - Markowitz, Martin; Sarafianos, Stefan G.
Abstract : Purpose of review: 4′-Ethynyl-2-fluoro-2′-deoxyadenosine (EFdA) is a nucleoside reverse transcriptase inhibitor (NRTI) with a novel mechanism of action, unique structure, and amongst NRTIs, unparalleled anti-HIV-1 activity. We will summarize its structure and function, antiviral activity, resistance profile, and potential as an antiretroviral for use in the treatment and preexposure prophylaxis of HIV-1 infection. Recent findings: EFdA is active against wild-type (EC50 as low as 50 pmol/l) and most highly NRTI-resistant viruses. The active metabolite, EFdA-triphosphate, has been shown to have a prolonged intracellular half-life in human and rhesus (Rh) blood cells. As a result, single drug doses tested in simian immunodeficiency virus mac251 -infected Rh macaques and HIV-1-infected individuals exhibited robust antiviral activity of 7–10 days duration. Preclinical studies of EFdA as preexposure prophylaxis in the Rh macaque/simian/human immunodeficiency virus low-dose intrarectal challenge model have shown complete protection when given in clinically relevant doses. Summary: EFdA is a novel antiretroviral with activity against both wild-type and NRTI-resistant viruses. As a result of the prolonged intracellular half-life of its active moiety, it is amenable to flexibility in dosing of at least daily to weekly and perhaps longer.